DETEKSI ETANOL SETELAH KONSUMSI ARAK DALAM URIN DENGAN GAS CHROMATOGRAPHY - Suaniti, N. M.; Astiti Asih, I. A. R.; Widya Astuti, N. P. (Jurnal Kimia (Journal of Chemistry); Vol. 6, No. 2 Juli 2012, 2013)
Ethanol is an alcohol which is in particular concentration allowed existing in beverages. One of alcoholic beverages that is popular in Bali is arak . This kind of beverage may contain ethanol in various concentrations depending on the distillation process carried out. The aim of this study was to detect the alcohol contents in urine collected from some volunteer who have consumed arak for two weeks with the technique of Gas Chromatography Flame Ionization Detector (GC-FID). The standard solutions employed were methanol, ethanol and acetic acid, while buthanol was used as the internal standard solution. The urine samples were collected in various sampling times after two weeks arak consumption. The ethanol contents obtained after 4, 8, 12, 16, 28, and 20 hours from the last consumption were (8.86 – 8.98) x 10 -2 , (8.06 – 8.46) x 10 -2 , (8,81 – 8.93) x 10 -2 , (7.47 – 7.73) x 10 -2 , (8.76 – 8.89) x 10 -2 , and (8.15 – 8.27) x 10 -2 % (b/v), respectively.
Keywords: ethanol, urine, Arak, Gas Chromatography